PELATIHAN KESEHATAN DAN KESELAMATAN KERJA (K3), SERVICE EXCELLENT, SERTA PENGELOLAAN SANITASI LINGKUNGAN TEMPAT WISATA DESA CATURHARJO, PANDAK, KABUPATEN BANTUL - mulasari, Surahma asti; Izza, Annisa Nurul; Masruddin, Masruddin; Hidayatullah, Farisa; P.B.M.A, Franciscus De; Axmalia, Astry (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2020)
The purpose of empowerment program is to make community ready to as a tourist destinations nature and culture while maintaining the value health , the community be able to apply occupational health and safety ( K3 ) And visitors to theofficers and The community can provide the best services in fulfilling the needs and expectations of tourists. The society such as the target counseling consisting of cadres, youth and Pokdarwis. Counseling and training done by using the method Lectures , the screening of video , follow up of the discussion as well as filling out of the questionnaires pre-post test About public knowledge that deals with tourism activities to be built by caturharjo village. The impact of this activity is to the local community and the village administration who want to embodying a tourist village this is Having knowledge of occupational health and safety In the tourism, So that the community or the management tours can give first aid and education to visitors when the accident on a visitor or a disaster happened.